Redescription of the monotypic plant bug genus Paraneella and Paraneella amazonica Carvalho 1954, with a neotype designation (Heteroptera: Miridae) - Minghetti, Eugenia (2023)
The monotypic Neotropical eccritotarsine genus Paraneella Carvalho (Heteroptera: Miridae) and its only included species, Paraneella amazonica Carvalho 1954, are diagnosed and redescribed, and new characters for their recognition are provided, illustrated, and photographed. Paraneella amazonica, previously known from the type locality in Brazil, is reported for the first time from Ecuador. Because the holotype deposited at the National Museum in Rio de Janeiro was destroyed by fire, a neotype is designated. Carvalho placed Paraneella in the “Neella-Neoneella genus complex” based on its similarity with Neella Reuter. The only existing key to identify these genera had in its first couplet characters referring to males that are unknown for Paraneella amazonica. A new key based on a new set of characters, which are photographed and illustrated, is provided.